COMPARISON OF THE QUALITY OF BALI AND LANDRACE PORK MEAT - I Putu Ardiawan; I Wayan Suardana; Kadek Karang Agustina (Fakultas Kedokteran Hewan Universitas Udayana, 2024)
Pigs are one of the meat-producing livestock commodities that have great potential to be developed because they have useful properties and abilities. Carcass and meat quality in general is influenced by factors before slaughter. Factors before slaughter that influence meat quality include genetics, breed, species, type of livestock, age, gender, feed including hormones, minerals and stress. This research aims to determine the differences in the quality of meat from Balinese pork and landrace pork, which genetically differ in terms of color, smell and consistency. The research design used is an observational design with a cross sectional sampling method because when collecting data the independent and dependent variables are observed together, collected once and at a time. The samples used in this research were 32 samples consisting of 16 samples of meat from Balinese pork and 16 samples of meat from landrace pork, then tested by 6 trained panelists. The research results were then tested using the Kruskal-Wallis test and if the results were significantly different, continue with the Mann Whutney test. The results showed that the color of the two meats showed significantly different colors (P<0.05), while in terms of smell and consistency the results showed no significant difference (P>0.05). It was concluded that Balinese pork and Landrace pork could not be differentiated in terms of smell and consistency, and there were visible differences in terms of color. It is recommended that future researchers who will continue research on meat organoletics carry out research immediately after the pig is slaughtered so that they can get maximum results.